The impact of physical environment on perceived safety of urban public space in Baghdad, Iraq - Hajiyat, Shahad R. M. (Universiti Putra Malaysia Press, 2021)
This paper aims to analyse the perceived safety in existing urban public spaces (UPS) in a war-torn city of Baghdad. One of the detrimental impacts of war is the destruction of the urban environment where it usually involved maximum physical damages which ultimately impacting the quality of life of its residents. Therefore, this study analyses the user’s perceived safety of three major UPS in Bab Al-Sharqi, Baghdad city (Tahrir Square, Alumma Park and Tayeran Square) in order to investigate the impact of war on UPS. The method used in this study is a mix method of qualitative and quantitative approaches that include a questionnaire survey, where the quantitative data explored using means ranking, ratios, and correlation tests. While qualitative data, of primary and secondary data collection, descriptively analysed. The study focuses on the three paradigms of the physical urban environment; legibility, permeability and the visual image, and their impact on the sense of safety. The findings reveal that the sense of safety at UPS in Baghdad is strongly determined by elements of the physical environment which were identified by the people, significant in the linear regression test, as being rickety (-2.584), visually dull (0.043) and physically incompatible (0.033). The perception of safety is also perceived differently by women than men. The sense of fear and apprehensiveness is larger among women respondents. This study contributes to identify set of strategies for UPS in terms of safety which can mitigate the impact of conflict and civil unrest in an urban setting.